I try to solve the following:

Let $X_1,X_2,\dots$ be independant random variables. We set $S_k=\sum\limits_{i=1}^kX_i$ for $k\geq 1$.

a) For $i\geq 1$ the random variables $X_i$ have a Poisson distribution with parameter $\lambda_i> 0$. What is the law of $S_k$

b) For $i\geq 1$, let $X_i$ have the binomial distribution with parameter $(n_i,p)$, where $n_i\in\mathbb{N}$ and $p\in[0,1]$. What is the law of $S_k$?

What I thought:

a) $$P(X_i=n)=e^{-\lambda_i}\frac{\lambda_i^n}{n!}$$

Since $X_1,X_2,\dots$ are independant we have: $$P(X_1=n,\dots,X_k=n)=P(X_1=n)\cdots P(X_k=n)=e^{-\lambda_1\dots-\lambda_k}\frac{(\lambda_1 \cdots \lambda_k)^n}{(n!)^k}$$

So the distribution is $$P(S_k\leq n)=\sum\limits_{l=0}^n e^{-\lambda_1\dots-\lambda_k}\frac{(\lambda_1 \cdots \lambda_k)^n}{(l!)^k}$$

b) $$P(X_i=l)=\binom{n_i}{l}p^l(1-p)^{n_i-l}$$

Since $X_1,X_2,\dots$ are independant we have: $$P(X_1=l,\dots,X_k=l)=P(X_1=l)\cdots P(X_k=l)=P(X_i=l)=\prod_{i=1}^k\binom{n_i}{l}p^l(1-p)^{n_i-l}$$

So the distribution is: $$P(S_k\leq n)=\sum\limits_{l=0}^n\prod_{i=1}^k\binom{n_i}{l}p^l(1-p)^{n_i-l}$$

But unfortunately I have a feeling that this is not correct.

  • $\begingroup$ The equations you have written are correct, but they do not address the distribution of the sum $S_k$. $\endgroup$ – André Nicolas Mar 24 '16 at 21:02
  • $\begingroup$ @AndréNicolas Is it now better? I really don't know how to solve this task. $\endgroup$ – Matriz Mar 24 '16 at 21:26
  • $\begingroup$ Do you know already that the sum of two independent Poisson is Poisson? Then the result for $k$ Poisson follows fairly quickly. As to the binomial, there is an informal way and a more formal way. If $X_1$ to $X_k$ are the numbers of successes in $n_1$ to $n_k$ trials, then $S_k$ is the number of successes in $n_1+\cdots+n_k$ trials. $\endgroup$ – André Nicolas Mar 24 '16 at 21:30

First, in Poisson case, $S_k \sim Pois(\sum_{i=1}^k \lambda_i)$ and in the binomial case, $S_k \sim Binom(\sum_{i=1}^k n_i, p).$

By intuition. Intuitively, these are sensible answers.

In the Poisson case, suppose you have $k$ radioactive sources, individually emitting particles at rates $\lambda_1, \lambda_2, \dots, \lambda_k.$ The number of particles $X_i$ emitted by each source is well modeled by a Poisson distribution, so that $X_i \sim Pois(\lambda_k).$ Then if we put all of the sources together, in combination it makes sense that the number of particles $S_k$ emitted by all sources will be Poisson with the sum of the rates of the individual sources: $S_k \sim Pois(\sum_{i=1}^k \lambda_i).$

In the binomial case, suppose the $i$th of $k$ students rolls a fair die $n_i$ times and counts the number of $X_i$ of 'sixes' seen. Then the distribution for each student will be $X_i \sim Binom(n_i, p = 1/6).$ Altogether, the $k$ students will have rolled a die $\sum_{i=1}^k$ times and the total number of 'sixes' seen will be $S_k \sim binom($\sum_{i=1}^k n_i, p = 1/6).$

Formally with MGFs. I don't know if you are familiar with moment generating functions. Both results follow from MGFs.

Poisson: The MGF for $X_i \sim Pois(\lambda_i)$ is $M_{X_i}(t) = \exp(\lambda_i(e^t - 1)).$ The MGF of the sum $S_k = \sum_{i=1}^k X_i$ is the product of the MGFs $M_{S_k}(t) = \prod_{i=1}^k M_{X_i}(t) = \exp(\Lambda(e^t - 1)),$ where $\Lambda = \sum_{i=1}^k \lambda_i.$ We recognize $M_{S_k}$ as the MGF of $Pois(\Lambda).$

Binomial: The MGF for $X_i \sim Binom(n_i, p)$ is $M_{X_i}(t) = (pe^t + (1-p))^{n_i},$ and the argument for the MGF of $S_k$ proceeds similarly.


I would suggest that the easiest way is to look at the case when $k=2$ and you can generalize it to the case when for $k=n$.

So, in general, If $X_i \sim Poisson(\lambda_i)$, then $X_1+\cdot\cdot\cdot+X_k=Poisson(\lambda_1+\cdot\cdot\cdot+\lambda_k)$

So it would instead be $$P(S_k=n)=e^{-(\lambda_1+\cdot\cdot\cdot+\lambda_k)}{(\lambda_1+\cdot\cdot\cdot+\lambda_k)}^n/n!$$

To start this proof, I would look at $$P(X_1+X_2=n)=\sum_{m=0}^nP(X_1=m)P(X_2=n-m)$$

For the binomial distribution,

$$X_1+\cdot\cdot\cdot+X_k \sim Bin(n_1+\cdot\cdot\cdot+n_k,p)$$

This can also be generalized from the case when $k=2$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.